THE INFLUENCE OF CREDIT RISK AND EFFICIENCY ON THE FINANCIAL PERFORMANCE OF CONVENTIONAL AND SHARIA BPRs IN EAST JAVA IN THE PERIOD BEFORE AND DURING THE PANDEMIC - Firman Wahyudi, Cahya; Muharam, Harjum (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2023)
This research study analyzes the influencecredit risk and efficiency on the financial performance of conventional and Sharia East Java BPRs in the period before and during the pandemic. Credit risk in this study uses NPL, NPF, LPP, while efficiency uses BOPO and CIR as independent variables.Financial performance in this study uses ROA, ROE, NIM ratios as dependent variables. In the research sample as many as251 BPR and 25 BPRS in East Java in the 2018-2021 period.Data analysis used a difference test between the average values of different groups using the sample t-test and ANCOVA test to analyze more than one dependent variable with the help of SPSS 26 software. The research results show that in hypotheses H1-a to H1-l, those that accept H0 are H1-c, H1-f, H1-g, H1-j, H1-k, which means there is no multivariate influence from the independent variable on the dependent variable. Meanwhile, the hypotheses H2-a to H2-l that accept H0 are H2-b, H2-g, H2-h, H2-i, H2-j, which means there is no multivariate influence from the independent variable on the dependent variable. in hypotheses H3-a to H3-f which accept H0 are H3-a, H3-b, H3-c which means there is no significant difference in the variable ratios before the pandemic between BPR and BPRS. in the hypotheses H4-a to H4-d which accept H0 are H4-a and H4-b meaning that there is no significant difference in the variable ratios before the pandemic between BPR and BPRS. in hypotheses H5-a to H5-d which accept H0 are H5-a, H5-b, H5-c and and H5-d means there is no significant difference in the variable ratios before the pandemic between BPR and BPRS.